Development of Pancasila Adventure Educational Game to Strengthen the Practice of Pancasila Values in Elementary School Students - Eni Rahmawati; Evany Sofia Prameswari; Imam Sumantri; Hanum Salsabila; Intan Dewi Anitasari; Nathania Benedicta Christabel (Lembaga Bale Literasi, 2025)
Pancasila as a way of life requires various methods to be internalized in daily life, one of which is through the creation of a game application to create an engaging and interactive learning experience. The game application will be named Pancasila Adventure, which aims to strengthen students' understanding of the implementation of Pancasila values. The material is evaluated through interactive quizzes with a points and rewards system. The reinforcement of Pancasila values can be instilled at various levels of education and types of schools, one of which is the Jogja Patriae Academy (JPA) theological school located in the city of Yogyakarta. JPA is a Christian educational institution that was originally a homeschooling program. JPA also supports the reinforcement of Pancasila values. This study aims to develop a Pancasila adventure educational game to strengthen the practice of Pancasila values among students. The type of research used is R&D development research with the ADDIE (Analyze, Design, Development, Implementation, Evaluation) model. The educational game was validated by media validators and material validators. The data collection techniques used in this research are interviews, observations, tests, and questionnaires.